EFEKTIVITAS SEDIAAN GEL DARI EKSTRAK Aloe vera SEBAGAI TERAPI ALTERNATIF PADA PENYEMBUHAN LUKA BAKAR DERAJAT II SECARA IN VIVO : Systematic Review - Nurul Sapphira Ersa Faisal (2022)
Second-degree burns are a condition that occurs quite often and needs to be treated appropriately. Apart from being treated with medical therapy, second-degree burns can also be treated with herbal plants, one of which is Aloe vera. Aloe vera has several compounds that are good for healing burns such as tannins, saponins, flavonoids, polyphenols, glucomannan, and acemannan. Then a good preparation to use on burns is gel because it has properties that quickly absorb, are not sticky, and cause a cold sensation on the skin. The purpose of this study was to present a publication on the effectiveness of gel preparations from Aloe vera extract as an alternative therapy for healing second-degree burns in in vivo study. The method used in this study is a Systematic Review, namely by conducting a literature search on gel preparations from Aloe vera extract on the healing of second-degree burns. The search was carried out through the PubMed, Google Scholar, and Science direct electronic databases using the PRISMA-P 2020 method and elimination using the JBI Critical Appraisal Checklist. The results of this study were obtained from 8 journals with good categories which concluded that gel preparations from Aloe vera extract were effective in healing second-degree burns, namely for a minimum duration of 5 days, an effective dose of at least 10%, then played a role in the mechanism of reducing burn area, percentage of closure. wound, epithelialization process, inflammatory process, and angiogenesis process (P<0.05). The conclusion of this study is that the preparation of Aloe vera extract gel is effective as an alternative therapy for healing second-degree burns.